Cyclic behaviour simulation of X38CRMOV5-47HRC (AISI H11)-tempered martensitic hot-work tool steel. (17th June 2008) - Ahmer, Z.; Velay, V.; Bernhart, G.; Rezai-Aria, F.
The cyclic behaviour of X38CrMoV5 (AISI H11) tool steel with a nominal hardness of 47HRC has been predicted. Basically, thermo-elastoplastic and thermo-elastoviscoplastic constitutive laws are investigated. First, various uniaxial isothermal conditions (LCF) with different strain rate, strain amplitude and temperature level are investigated. Then the constitutive laws are examined under various TMF loading conditions. The simulated results by both the approaches are compared with experimental results in terms of stress?strain behaviour and cyclic softening. Some applications of the model for simulation of thermal fatigue sample are shown. Taking into consideration the results of this work, the goal is to further characterise the limitations of these constitutive laws under complex and severe loading conditions, i.e., under variable temperature, variable strain amplitude and thermal fatigue structural specimen.